Rapid co-sintering enables ultra-narrow pore size distribution ceria membranes for high-selectivity U(VI)/V(V) separation - Huanyu Zhou; Fan Yu; Minghui Qiu; Xiaowei Da; Xianfu Chen; Kaiyun Fu; Yiqun Fan (Chemical Engineering Journal, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Thermal Tolerance of Geographical Populations and Their Hybrids in the Ivory Shell Babylonia areolata - Jingqiang Fu; Linwei Nie; Zhenzhen Cai; Weiguang Zou; Yuan Liang; Wengang Lü; Minghui Shen; Xuan Luo; Weiwei You; Tuanyu Guo; Caihuan Ke (Fishes, 2026)
Global warming and summer heatwaves increasingly threaten the survival of cultured Babylonia areolata, but the heat tolerance of different geographical populations and the potential for genetic improvement by hybridization remain poorly understood. In this study, four geographical populations (Thailand, TL; Wanning, WN; Zhao’an, ZA; Changle, CL) and four hybrid combinations (TH, HT, TF, and FT) were compared for mortality rate, median lethal temperature (LT50), and critical thermal maximum (CTMax) under controlled thermal stress. The results showed that the low-latitude TL population exhibited significantly higher LT50 (36.49 ± 0.05 °C) and CTMax (35.77 ± 0.52 °C) than the high-latitude CL and ZA populations (LT50: 35.90 ± 0.05–36.02 ± 0.04 °C; CTMax: 35.12 ± 0.77–35.26 ± 0.53 °C). All four hybrids had improved heat tolerance compared with their low parents, with TH and HT showing the strongest mid-parent heterosis (e.g., 73.68–78.94% for survival at 36.5 °C). However, none significantly exceeded the high-parent performance (TL), indicating only mid-parent heterosis. These findings reveal significant genetic variation in heat tolerance among geographical populations of B. areolata and confirm that cross-breeding can effectively enhance heat tolerance, though it does not produce transgressive superiority. This study provides key genetic resources and a theoretical basis for breeding heat-tolerant strains of B. areolata.

Synthesis and fungicidal activity of novel 1,1-diaryl-2-azolylethanols with a pyridine moiety - Minghui Chen; Fahong Yin; Sai Hong; Yanfei Liu; Bin Fu; Yumei Xiao; Xuemin Wu; Zhaohai Qin (Molecular Diversity, 2026)

Physiological Effects and Yield Potential of Japonica Rice Grown Using Straw-Based Substrate Blocks and Seedbed Conditioner - Yunsheng Song; Yi Jiang; Fei Chen; Minghui Dong; Xiuliang Jin; Yajie Hu; Yu Fu; Zhongying Qiao; Yuxuan Wang (International Journal of Plant Production, 2026)

High-efficient and reusable frictional-dissipating metamaterial based on compression-torsion coupling mechanism - Wen Jiang; Minghui Fu; Yanbin Wang; Hao Wu; Lingling Hu (Engineering Structures, 2026)

Ceramic membrane contactors for removing ammonia from wastewater: 2D model establishment and module scaling-up - Shiji Sun; Kexin Zhang; Dawei Gong; Kaiyun Fu; Xianfu Chen; Minghui Qiu; Ping Luo (Journal of Environmental Chemical Engineering, 2026)

Ceramic membranes for desalination: Design and fabrication strategies based on the sol-gel method - Weida Shi; Jing Wang; Xianfu Chen; Kaiyun Fu; Minghui Qiu; Yiqun Fan (Desalination, 2026)

Insight into the meat quality differences of Tibetan sheep from different altitudes based on metabolomics - Ruisi Liu; Jianing Fu; Shaobo Li; Minghui Gu; Liang Li; Le Xu; Jiangying Yu; Dequan Zhang; Li Chen (Food Chemistry, 2026)

Overexpression of DWARF14-LIKE2 in Arabidopsis thaliana alters multiple traits related to plant morphology and osmotic and salt stress tolerance - Xiaofan Nie; Liangliang Li; Chenbo Zhu; Kaixin Yang; Qingtian Li; Jiahe Fu; Minghui Xing; Mingming Wang; David C. Nelson; Xianzhong Feng; Jiuhai Zhao; Zhengwei Liang; et al. (Plant Cell Reports, 2026)

Integration of major ions and multiple isotopes to identify circulation and hydrochemical process of limestone groundwater in the Huainan coalfield, China - Miao Zhang; Luwang Chen; Xiaowei Hou; Elena Secco; Yongsheng Hu; Baoxin Zhao; Minghui Wu; Xianjie Fu (Journal of Contaminant Hydrology, 2026)

Mining and Analysis of Terpene Synthase Genes in Cinnamomum Plants - Jiahao Liang; Minghui Fu (Tropical Plant Biology, 2025)

Evaluation of harmful impact of low concentration cylindrospermopsin through zebrafish behavioral endpoints under multiple life stages - Minghui Fu; Yining Zhang; Linjie Luo; Minglu Wu; Liyan Teng; Jiandong Mu; Guohua Xiao; Yanyang Xu; Jing Qiu; Tingting Chai; Yongzhong Qian; Guijie Hao; et al. (Journal of Hazardous Materials, 2025)

Ribavirin showed insect growth regulator activity to Helicoverpa armigera - Li Xu; Yin Huang; Zezheng Liu; Qi Zuo; Minghui Long; Yichen Fu; Runqiang Liu; Yunchao Kan; Dongzhi Li (Journal of Asia-Pacific Entomology, 2025)

Clustering Analysis of Natural D-borneol Resource Plants Based on Simple Sequence Repeat (SSR) Markers, Leaf Morphology, and Chemical Composition - Ziqing Lu; Zhuolin Ma; Minghui Fu; Jianyu Su (Biochemical Genetics, 2025)

Development of a sex-specific molecular marker reveals the ZW/ZZ sex-determination system in Babylonia areolata (link 1807) - Yu Zou; Yuan Liang; Xuan Luo; Weiwei You; Minghui Shen; Jingqiang Fu; Caihuan Ke (Aquaculture, 2025)

The application of pressure-driven ceramic-based membrane for the treatment of saline wastewater and desalination–A review - Yuehua Zhang; Ting Chen; Xianfu Chen; Kaiyun Fu; Minghui Qiu; Yiqun Fan (Desalination, 2025)

Corrigendum to ‘The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system’ [Environ. Pollut. 364P1 (2024) 125311] - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

A novel nested compression-torsion metamaterial with independently customized mechanical properties - Wen Jiang; Minghui Fu; Lingling Hu; Yanbin Wang; Hao Wu (Engineering Structures, 2025)

Overlooked emerging polycyclic aromatic hydrocarbons and benzofuran derivatives in soil from coking plant - Qiaofeng Ai; Lirong Gao; Jiyuan Weng; Xiaoying Cao; Yang Liu; Xin Cheng; Yingxin Zhang; Qianling Yang; Meijun Li; Jing Yang; Qiang Fu; Xuan Zheng; et al. (Science of The Total Environment, 2024)

A straightforward strategy to modulate ROS generation of AIE photosensitizers for type-I PDT - Zhencheng Sun; Jiaxin Wang; Minghui Xiao; Kaiyu Wu; Cheng Wang; Hao Fu; Shuyi Lv; Linqi Shi; Chunlei Zhu (Chemical Engineering Journal, 2024)

Oryza glumaepatula and calcium oxide nanoparticles enhanced Cr stress tolerance by maintaining antioxidant defense, chlorophyll and gene expression levels in rice - Humera Ashraf; Fozia Ghouri; Minghui Zhong; Sardar Alam Cheema; Fasih Ullah Haider; Lixia Sun; Shafaqat Ali; Mohammed Ali Alshehri; Xuelin Fu; Muhammad Qasim Shahid (Journal of Environmental Management, 2024)

Liriodendrin stimulates proliferation and milk protein synthesis of mammary epithelial cells via the PI3K-DDX18 signaling - Youwen Qiu; Mingming Fu; Minghui Zhang; Bo Qu; Zhen Zhen (In Vitro Cellular & Developmental Biology - Animal, 2024)

Reduction of haemoglobin is related to metal mixtures exposure in Chinese preschoolers: Joint effect models - Ye Fu; Minghui He; Yang Liu; Mingzhu Li; Meiqin Zhu; Yan Wang; Wei Lin; Lili Yu; Liting Yang; Yao Zhang; Yanli Liu; Hongxian Ji; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

The interaction effects of zinc and polygenic risk score with benzo[a]pyrene exposure on lung cancer risk: A prospective case-cohort study among Chinese populations - Ming Fu; Hua Meng; Minghui Jiang; Ziwei Zhu; Xin Guan; Yansen Bai; Chenming Wang; Yuhan Zhou; Shiru Hong; Yang Xiao; Meian He; Xiaomin Zhang; et al. (Environmental Research, 2024)

Associations Between Exposure to Metal Mixtures and Insufficient Bone Strength: A Cross-Sectional Study Among Children Aged 2–6 Years - Yanli Liu; Yan Wang; Ye Fu; Yang Liu; Mingzhu Li; Minghui He; Yao Zhang; Chen Li; Hongcheng Ding; Xiaowen Li; Hongxian Ji; Jing Wang (Exposure and Health, 2024)

A near-infrared/tumor microenvironment dual-responsive cobalt-based material for photothermal/photodynamic/DNA-damaging chemotherapy synergistic therapy and anti-inflammation - Shuanglong Tang; Na An; Jing Luan; Xiaodan Wen; Yutuo Fu; Minghui Gao; Chongshen Guo (Chemical Engineering Journal, 2024)

Survival and immune responses of two populations of Babylonia areolata and their hybrids under pathogenic Vibrio challenge - Jingqiang Fu; Yuan Liang; Minghui Shen; Wengang Lü; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2024)

A composite prismatic structure with thermal-torsion coupling effect - Wei Chen; Rongchang Zhong; Hao Wu; Nan Sun; Minghui Fu; Dingshu Xiao (Engineering Structures, 2024)

Impact of nanoplastics on Alzheimer ’s disease: Enhanced amyloid-β peptide aggregation and augmented neurotoxicity - Xiaoli Gou; Yongchun Fu; Juan Li; Juan Xiang; Minghui Yang; Yi Zhang (Journal of Hazardous Materials, 2024)

Bisphenol chemicals in colostrum from Shanghai, China during 2006–2019: Concentration, temporal variation, and potential influence on birth parameters - Xiaolan Zhang; Minghui Fu; Kexin Li; Xiaomeng Cheng; Xinyu Zhang; Xiuhua Shen; Bingli Lei; Yingxin Yu (Food and Chemical Toxicology, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Deploying photovoltaic arrays in degraded grasslands is a promising win-win strategy for promoting grassland restoration and resolving land use conflicts - Bin Zhang; Ruohui Zhang; You Li; Shiwen Wang; Minghui Zhang; Fu Xing (Journal of Environmental Management, 2024)

Non-target and target analysis to identify and characterize thiophenes in soil from an abandoned coking plant - Qiaofeng Ai; Lirong Gao; Di Huang; Jing Yang; Qiang Fu; Xuan Zheng; Yang Liu; Lin Qiao; Jiyuan Weng; Minghui Zheng (Journal of Hazardous Materials, 2023)

Mechanical properties of re-entrant chiral anisotropic honeycomb - Mingming Chen; Rongchang Zhong; Yunzhou Wang; Hao Wu; Minghui Fu (Engineering Structures, 2023)

In Silico Genome-Wide Mining and Analysis of Terpene Synthase Gene Family in Hevea Brasiliensis - Jiahao Liang; De Wang; Xin Li; Weiwen Huang; Chun Xie; Minghui Fu; Hongmei Zhang; Qiong Meng (Biochemical Genetics, 2023)

Organophosphate tri- and diesters in source water supply and drinking water treatment systems of a metropolitan city in China - Xiaolan Zhang; Yuhao Bi; Minghui Fu; Xinyu Zhang; Bingli Lei; Xin Huang; Zhenzhen Zhao (Environmental Geochemistry and Health, 2023)

Secondary pollution of microplastic hetero-aggregates after chlorination: Released contaminants rarely re-adsorbed by the second-formed hetero-aggregates - Yan Jin; Minghui Li; Feiyong Chen; Lin Wang; Lijie Zhang; Zhigang Yang; Ning Wang; Jie Fu; Yang Yu; Xiaoxiang Cheng; Daoji Wu (Journal of Hazardous Materials, 2023)

Translation, ribosome biogenesis, and oxidative damage caused by chlorpyrifos exposure to common carp (Cyprinus carpio L.) liver: application of combined RNA-seq with sRNA-seq in risk evaluation of environmental toxicant chlorpyrifos - Jing Fu; Minghui Wang; Maria T. Chaudhry; Hongfei Xue; Lichun Zhang; Yanhua Huang; Chunpeng Liu (Environmental Science and Pollution Research, 2021)

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

Callus induction and plant regeneration of Spirodela polyrhiza - Mingxing Huang; Xiaoyu Ma; Yanshan Zhong; Qinxia Hu; Minghui Fu; Yali Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

IgG4-related inflammatory pseudotumor of the brain parenchyma: a case report and literature review - Zhuqing Zhang; Weiwei Fu; Minghui Wang; Lei Niu; Bin Liu; Yingbin Jiao; Xuejun Liu (Acta Neurologica Belgica, 2018)

LC–MS/MS-Based Metabolome Analysis of Biochemical Pathways Altered by Food Limitation in Larvae of Ivory Shell, Babylonia areolata - Jingqiang Fu; Minghui Shen; Yawei Shen; Wengang Lü; Miaoqin Huang; Xuan Luo; Jinjin Yu; Caihuan Ke; Weiwei You (Marine Biotechnology, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Acute psychoactive and toxic effects of D. metel on mice explained by 1H NMR based metabolomics approach - Yonghong Fu; Zhihong Si; Pumin Li; Minghui Li; He Zhao; Lei Jiang; Yuexiao Xing; Wei Hong; Lingyu Ruan; Jun-Song Wang (Metabolic Brain Disease, 2017)

Codon usage bias in herpesvirus - Minghui Fu (Archives of Virology, 2010)